POST HATCH PERFORMANCE OF MEAT TYPE JAPANESE QUAIL INFLUENCED BY TIME OF OFFERING FEED AND AMBIENT ENVIRONMENT - J. Hussain; S. Mehmood; I. Ullah; A. Mahmud; A. Ghayas; M. Usman; A. Rehman; S. Ahmad (Journal of Animal and Plant Sciences, 2019)
Present study evaluated the effect of time of offering feed and ambient environment on growth, morphometric and carcass traits in Japanese quail chicks.Nine hundred chicks hatched from prior incubated eggs were distributed in 5 feeding and environmental regimes (FR) having 9 replicates of 20 birds each under completely randomized design. In FR0, conventional hatching was practiced; chicks hatched from prior incubated eggs remained in hatcher till the end of incubation (17 days) without any provision of feed and water. In FR1, provision of feed and water was ensured to newly hatched chicks just after hatching and were shifted to rearing house after 17 days of incubation, while in FR3, FR5&FR7, newly hatched chicks were brooded within the same hatcher for an extra 3, 5 and 7 days along with provision of feed and water. Different FR strategies significantly influenced overall body weight, body weight gain, and times of gain.FR strategies also affected body, drumstick, keel, and shank length, wing spread, drumstick and shank circumference as well as thigh, liver and heart weight. On overall basis, FR3 and FR5 proved to be the best in terms of overall growth performance and morphometric traits respectively.
Keywords: Japanese quail; feeding and environmental regimes; Growth; Morphometric; Carcass traits